Generic representations in L-packets - Mishra, Manish (International journal of number theory, 2015)
We give the details of the construction of a map to restate a conjecture of Gan, Gross and Prasad about adjoint group action on generic representations in L-packets. We give an application of the construction to give another proof of the classification of the Knapp-Stein R-group associated to a unitary unramified character of a torus. Finally, we prove the conjecture for unramified L-packets.
Gesehen am 20.03.2018